2002
DOI: 10.1139/f02-136
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the reproductive potential of local populations of coastal Atlantic cod (Gadus morhua)

Abstract: We investigate the feasibility of enhancing the reproductive potential of northern Atlantic cod (Gadus morhua L.) populations resident in Newfoundland and Labrador bays by "catch, grow out, and release". This entails trapping juvenile and young adult fish from the local population, increasing their growth, maturation rate, and potential fecundity by feeding them a natural diet in net pens, and then returning the fish to their natal bay habitat to spawn. To determine whether multiyear farming affects spawning s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
3
4
0
Order By: Relevance
“…Farmed cod dispersal rates after release were similar to previous work; however, wild cod dispersal rates were slower (12 h for 90% dispersal compared with only 3 h for 100% dispersal observed by Wroblewski and Hiscock (2002)). Differences in seasonal activities such as migration and feeding may affect dispersal rate, as cod released in August dispersed more slowly than those released in October, and both dispersed more slowly than the cod released in late April and early May by Wroblewski and Hiscock (2002) (wild juveniles reared in captivity for 3 years prior to release). Furthermore, we detected few fish from December until April, suggesting that during winter the cod were avoiding the cold shallow coastal waters Fig.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Farmed cod dispersal rates after release were similar to previous work; however, wild cod dispersal rates were slower (12 h for 90% dispersal compared with only 3 h for 100% dispersal observed by Wroblewski and Hiscock (2002)). Differences in seasonal activities such as migration and feeding may affect dispersal rate, as cod released in August dispersed more slowly than those released in October, and both dispersed more slowly than the cod released in late April and early May by Wroblewski and Hiscock (2002) (wild juveniles reared in captivity for 3 years prior to release). Furthermore, we detected few fish from December until April, suggesting that during winter the cod were avoiding the cold shallow coastal waters Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Few studies have quantified the recapture rate of escaped farmed cod; however, results from an acoustic telemetry study in Norway (Uglem et al 2008) as well as from stock enhancement studies (Svåsand et al 2000;Skilbrei and Jørgensen 2010) suggest that the incidental recapture rates may be high (30%-44%) with even a modest fishing effort. While there was no dedicated recapture fishery near Bay Bulls, rates of incidental fishery recaptures did not differ between escapee farmed (11%) and wild cod (10%; similar to Brattey et al 2008), in contrast with previous studies (Wroblewski and Hiscock 2002;Uglem et al 2008). The timing and recapture locations in this study reflect the pattern of seasonal (i.e., summer) small-scale fisheries (recreational, sentinel, and commercial) at the mouth of Bay Bulls and off Petty Harbour.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Similarly, Wroblewski and Hiscock (2002) demonstrated that wild cod held in cages for several growing seasons would reintegrate into wild populations in spawning areas when returned to the wild. However, these ''farmed'' cod were slower to disperse from the release point and were caught at higher rates in fisheries than wild cod.…”
Section: Discussionmentioning
confidence: 98%